Water quality Part 2. Physical, chemical and biochemical methods Sec 2.35 Method for determination of electrical conductivity (BSI, 1989)
Water, Quality, Water testing, Water resources, Resistance measurement, Test equipment, Electrodes, Error correction, Testing conditions, Precision